2006
DOI: 10.1371/journal.pmed.0030299
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Health Research Capacity Building: An Evidence-Based Tool

Abstract: Bates and colleagues describe the development of a tool to assess capacity-building programs in health research, which they used in Kumasi, Ghana.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
111
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(115 citation statements)
references
References 6 publications
1
111
0
Order By: Relevance
“…Our study demonstrated the value of providing opportunity for nurses and health disciplines to engage in CPBR and undertake a project relevant to clinical practice that adds to the body of knowledge on the value of collaborative practice based research capacity building strategies [6][7][8][15][16][17] and communities of practice. [22,27,28] Despite the valuing of the experience, challenges emerged that necessitate future efforts to provide support for nurses and health disciplines participating in research capacity building strategies.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…Our study demonstrated the value of providing opportunity for nurses and health disciplines to engage in CPBR and undertake a project relevant to clinical practice that adds to the body of knowledge on the value of collaborative practice based research capacity building strategies [6][7][8][15][16][17] and communities of practice. [22,27,28] Despite the valuing of the experience, challenges emerged that necessitate future efforts to provide support for nurses and health disciplines participating in research capacity building strategies.…”
Section: Resultsmentioning
confidence: 84%
“…[14] Further, despite efforts to build research capacity through a variety of initiatives (e.g. educational programs, fellowships, funding), [6][7][8][15][16][17] nurses and health care professionals continue to report lacking skills and confidence to conduct research due to minimal or no experience and not having enough time to participate in research. [1,6,12,14,[18][19][20][21] In this context, an Academic Health Sciences Center (AHSC) developed and hosted a competitive grants competition with a comprehensive learning approach as part of a larger strategy aimed at building CPBR.…”
Section: Introductionmentioning
confidence: 99%
“…As stated in the introduction to this article, Bates et al (2006) and Lansang and Dennis (2004) explain it as the improvement of the abilities of individuals, organisations and systems to conduct research and disseminate quality reports, a definition compatible with the Cooke integrated framework. In reviewing other studies on the topic, it becomes clear that the term, research capacity building, is subjective and tends to be context-specific and therefore difficult to define (Levine et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Research capacity development varies in focus. Bates et al (2006) and Lansang and Dennis (2004) explain it as the improvement of the abilities of individuals, organisations and systems to conduct research and disseminate quality reports. A strong emphasis in research production and dissemination is placed on knowledge translation and uptake (Edwards, Kaseje, and Kahwa 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence informed policy making depends on the capacity of policy makers to use such reviews and the capacity of researchers to produce them. That each of these capacities needs the other is apparent for research about both health (Cooke 2005) and international development (Bates et al 2006); and has been shown to be applicable to the production of systematic reviews (Oliver et al 2015a). These capacities need to be matched by timeliness and relevance of evidence to inform policy dilemmas (Oliver K et al 2014;Whitty 2015).…”
Section: Introductionmentioning
confidence: 99%